The charismatic spirituality of Abraham Joshua Heschel mystical teachings of an American rabbi - Breslauer, S. Daniel (Lewiston : Edwin Mellen Press, 2011)
This is a reflection on the teachings of Abraham Joshua Heschel, a teacher to an entire generation of rabbis. Breslauer looks at Heschel as an "ethical scholar," a teacher of both Jewish and non-Jewish traditions, and a Jewish Kabbalah mystic. The book addresses Heschel's concern that a spiritual crisis existed for all religions. In particular, Breslauer's examination of Heschel's development of the "depth-theology" concept to address the spiritual crisis is the central focus of this book. Breslauer draws attention to Hesechel's use of Jewish tradition and his understanding of God, not as a ph.
Introduction: Abraham Heschel, depth theology and charismatic spirituality -- Chapter One. Charismatic spirituality, Abraham Joshua Heschel and depth-theology -- Chapter Two. Heschel and the spiritual personality -- Chapter Three. Abraham Heschel, charismatic spirituality and the nightmare of history -- Chapter Four. Heschel, culture, spirituality and generosity -- Chapter Five. Questioning civilizations: Heschel, spirituality and caution -- Chapter Six. Heschel, ritual and charismatic spirituality -- Selected bibliography -- Index.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Heschel, Abraham Joshua, -- 1907-1972 -- Teachings; Spiritual life -- Judaism; Heschel, Abraham Joshua -- 1907-1972 -- Teachings; Spiritual life -- Judaism; Spirituality; Religion; RELIGION / Judaism / Theology; Electronic books